Covid-19 as a Mean of Emerging Structural Coupling in Tourism. Review from Functional Systems - Enríquez Martínez, Mario Alberto; Vázquez Ramírez, Diana (MAD, 2024)
The study of tourism in the second half of the twentieth century focuses on systemic thinking, exposing it as a structure composed of different components that interact with each other and allow it to be explained from the social field. Niklas Luhmann's Functional Systems Theory enables the analysis of tourism as a form of structural coupling between the different functional systems that make up the societal system, to which are added emerging situations such as the pandemic derived from covid-19; therefore, it is established that the function that tourism and pandemic fulfill within society, falls in the form of a means of structural and operational coupling between functional systems. Derived from the second-order observation based on a documentary review, the emergence of emerging forms of communication related to tourism from the economic, political and medical systems is shown. Trends such as virtual tours from the internet of things, eco-friendly tourism, slow travel, bleisure travel, among others, make manifest the importance that emerging events such as the most recent pandemic, maintain in the reconfiguration of the tourism sector in the so-called new normality.